2001
DOI: 10.3168/jds.s0022-0302(01)74541-9
|View full text |Cite
|
Sign up to set email alerts
|

Composition of Growth of Holstein Calves Fed Milk Replacer from Birth to 105-Kilogram Body Weight

Abstract: Sixty calves were assigned to a comparative slaughter study to determine the changes in composition of milk replacer-fed Holstein bull calves from birth to 105-kg body weight (BW). Six calves were slaughtered on day of birth and served as a baseline for comparison of compositional changes. Fifty-four calves were assigned to one of three treatments (18 calves per treatment). Calves were fed milk replacer containing 30% crude protein (CP) and 20% fat. Target growth rates for treatments 1, 2, and 3 were 500, 950,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

36
185
11
13

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 207 publications
(245 citation statements)
references
References 22 publications
36
185
11
13
Order By: Relevance
“…Values for stage 1 are in agreement with earlier reports (Diaz et al, 2001) but are higher than more recent studies (Blome et al, 2003). Values for stages 2 and 3 are consistent with values measured by van den Borne et al (2006) in calves of similar BW.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Values for stage 1 are in agreement with earlier reports (Diaz et al, 2001) but are higher than more recent studies (Blome et al, 2003). Values for stages 2 and 3 are consistent with values measured by van den Borne et al (2006) in calves of similar BW.…”
Section: Discussionsupporting
confidence: 92%
“…Values for the first stages are in agreement with previous results (Donnelly and Hutton, 1976;Diaz et al, 2001) with calves receiving high quantities of protein in their diets and they are also close to the value used by the NRC (187 g/kg BW gain, NRC, 2001). However, the protein content of BW gain for the oldest calves is higher than that measured by Meulenbroeks et al (1986) or values measured previously in our group (Labussiè re et al, 2008b), although they are consistent with results of Vermorel et al (1974).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Accordingly, performance in the current study was in line with that reported elsewhere. However, these growth rates are significantly lower than the .1 kg/day claimed as achievable by Drackley (2000) and observed by Diaz et al (2001) when high levels of MR are offered.…”
Section: Discussionmentioning
confidence: 56%
“…The aim of this 'accelerated' growth regime is to exploit the high lean tissue growth potential of young calves and promote greater lean growth without fattening. Diaz et al (1998 and showed that feeding a MR of 300 g/kg CP increased lean tissue deposition without fattening, whereas Blome et al (2003) and Bartlett et al (2006) showed that it increased MR protein concentration while maintaining a constant energy density and decreased body fat content. It is important to note that calves in these studies were offered a liquid diet with no supplementary starter concentrates.…”
Section: Introductionmentioning
confidence: 99%